Análise do conforto térmico em residências unifamiliares no município de Pau dos Ferros/RN - Azevedo, Ronny Kley Queiroz de (Universidade Federal Rural do Semi-Árido, 2018)
According to the majority of authors, there is a growing concern about the optimum performance of housing in relation to thermal, acoustic, and environmental comfort, among others, adapting the buildings and their architecture to the needs of man. The concept of thermal comfort encompasses man's satisfaction with the thermal environment in which he finds himself; such a concept involves balancing the heat produced by the body with the heat lost to the environment. With this study, it will be possible to obtain relevant data to evaluate the performance of the desired thermal comfort, the main objective of the study, taking into account the climatic conditions of the region where the study will be done and the types of materials used in the construction of the property. It is known that the performance of thermal comfort surveys aim to analyze and propose conditions that help in the design of an adequate environment for human permanence, as well as the activities that will be performed in that environment. The factors that influence the performance of thermal comfort in single-family homes have been increasingly debated, especially in our region whose climate has peculiar characteristics, such as high temperatures and low rainfall rates, so a control is necessary to be able to present all the necessary requirements according to existing standards in construction, such as NBR 15.220 / 2003. The objective of this study is to analyze the performance of thermal comfort according to constructive aspects, thermal sensations of the residents and parameters foreseen by the standard that is used in the study, which parameters will be confronted with the existing situations in order to evaluate if the housing is compatible with its ideal specifications of fences and roof. From the analysis, the buildings not being in agreement with the specifications of NBR 15.220 / 2003 thus, will be presented alternatives of constructive techniques (type and form of brick laying, for example) appropriate to the region of the study as well as ways of improving the (windows with suitable openings, for example) to achieve a desired thermal performance. Therefore, it can be noted that the buildings considered in the study, concomitant to most of the buildings of the region that present the same constructive characteristics, are not providing their residents with adequate thermal comfort conditions according to the region in which they are located.
Keywords: Conforto Ambiental; Desempenho Térmico; Construção civil; Environmental Comfort; Thermal Performance; Construction; ENGENHARIAS::ENGENHARIA CIVIL